Safety of PD-1/PD-L1 Inhibitors Combined With Palliative Radiotherapy and Anti-Angiogenic Therapy in Advanced Hepatocellular Carcinoma - Zhong, Liting; Wu, Dehua; Peng, Weiwei; Sheng, Hailong; Xiao, Yazhi; Zhang, Xuebing; Wang, Yuli (Frontiers in Oncology, 2021)
Background: Previous studies have explored cancer immunotherapy with radiotherapy or anti-angiogenic therapy, but no trials have reported a triple therapy approach. This study aimed to investigate safety and clinical outcome of PD-1/PD-L1 inhibitors combined with palliative radiotherapy and targeted angiogenesis therapy in hepatocellular carcinoma (HCC) of Barcelona Clinic Liver Cancer (BCLC) stage C. Methods: Consecutive patients (n=16) treated with PD-1/PD-L1 inhibitors combined with radiotherapy and anti-angiogenic therapy in a bi-institutional cohort between July 2017 and December 2020 were retrospectively included. Radiotherapy was conducted within 14 days of the first administration of immunotherapy. The primary endpoint was treatment-related adverse event (TRAE). Results: The median follow-up was 383 days. Fifteen patients (93.8%) experienced at least 1 TRAE. The most common TRAEs of any grade were rash (25%), diarrhea (25%), aspartate aminotransferase increase (18.8%), alanine transaminase increase (18.8%), decreased appetite (18.8%), and fatigue (18.8%). Grade 3/4 TRAEs occurred in 4 patients (25%) and finally led to treatment interruption. No patient death was attributed to treatment. No specific events were responsible for the addition of radiotherapy. Six patients showed partial response, 7 showed stable disease, and 2 showed progressive disease. The objective response rate and disease control rate were 40.0% (95% CI 16.3%–67.7%) and 86.7% (95% CI 59.5%–98.3%), respectively. Moreover, the median progression-free survival was 140 days. Patients had a median overall survival of 637 days, and the estimated rates of survival at 6 and 12 months were 92.3% and 75.5%, respectively. Conclusion: PD-1/PD-L1 inhibitors combined with palliative radiotherapy and anti-angiogenic therapy appear to be safe, with no unexpected adverse events. Additional studies exploring the clinical benefit are warranted.